ANALISIS KUALITAS PELAYANAN DANA PENSIUN PT TASPEN (PERSERO) KANTOR CABANG UTAMA SEMARANG - Widi Warsita; Endang Larasati Setianingsih; Mochammad Mustam (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
This study aims to assess the quality of service retirement fund PT. TASPEN (Persero) Main Branch Office in Semarang and to describe the factors that affect the quality of service in TASPEN PT (Persero) KCU Semarang. The problems that exist in this research is the employee's performance is still less than optimal in providing services. This study was conducted to determine the level of quality of service and to determine the factors that affect the quality of service. In this study, the method used is ekplanator, the type that is used to examine the relationship variables studied. Data obtained based on questionnaires given to 96 participants retiring as a respondent in TASPEN PT (Persero) KCU Semarang. These results indicate that the quality of care judged by the level of performance and the level of Importance is above the average value of the minimum levels of performance and level of importance of service. Implementation of the service is a priority PT TASPEN (Persero) KCU Semarang main priorities of the Cartesius diagram is in quadrant A the ease of access, the certainty of the time, the justice ministry and the security services. For factors that affect the quality of services obtained results showed the presence of a positive and significant correlation with the variable that is no awareness of the correlation coefficient of 0.412 and rules with correlation coefficient 0.572. From the results of these studies PT. TASPEN (Persero) KCU Semarang could improve services seen from a high level of interest by participants who considered retiring but low at the performance of employees ease of access, time and security assurance services. Then increase the awareness of every employee and rules set by the agency.